Buyers Beware: Lead Poisoning due to Ayurvedic Medicine - Pierce, J. Matthew R. (Springer-Verlag, 2012)
A 29-year-old man, who recently emigrated from India, presented with a 2-week history of abdominal pain, as well as nausea, constipation, and fatigue. He underwent removal of a parathyroid adenoma 6 weeks prior to admission and received a locally made Indian traditional medicine (Ayurveda) for pain control; however, this information was not initially available. He was instructed to take approximately 15 g/day. Initial evaluation revealed a normocytic anemia, but other workup including imaging and endoscopy was unrevealing. Given his recent use of Ayurvedic medicines, we tested for lead poisoning and found a blood lead level of 72 mcg/dl. We sent his medicine for analysis and found it had a high lead concentration of 36,000 mcg/g, which is over 25,000 times the maximum daily dose. He improved with cessation of the medicine and treatment with succimer. Lead poisoning can present with a variety of nonspecific signs and symptoms, including abdominal pain and anemia. Ayurvedic medicines, as well as traditional medicines from other cultures, may be a source of lead or other heavy metals. It is essential for physicians to be aware of adverse effects of Ayurvedic medicines as they are easily available and increasing in popularity.